2015
DOI: 10.1155/2015/825068
|View full text |Cite
|
Sign up to set email alerts
|

The Lyophilization Process Maintains the Chemical and Biological Characteristics of Royal Jelly

Abstract: The alternative use of natural products, like royal jelly (RJ), may be an important tool for the treatment of infections caused by antibiotic-resistant bacteria. RJ presents a large number of bioactive substances, including antimicrobial compounds. In this study, we carried out the chemical characterization of fresh and lyophilized RJ and investigated their antibacterial effects with the purpose of evaluating if the lyophilization process maintains the chemical and antibacterial properties of RJ. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…This value was similar to our results for the same strain (Table 1). Conversely, fresh RJ purchased in Brazil and used by Nascimento et al (2015) appeared to exhibit stronger antimicrobial activity (MICs, 1.55% and 0.78% [w/v] for P. aeruginosa ATCC 27853 and E. coli ATCC 25922 respectively) than the Japanese RJ used in this study (Table 1). Therefore, further studies are needed to verify the universality of our results in M. plutonius strains belonging to different sequence types and clonal complexes and RJ originating from bee strains differing in their genetic background.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This value was similar to our results for the same strain (Table 1). Conversely, fresh RJ purchased in Brazil and used by Nascimento et al (2015) appeared to exhibit stronger antimicrobial activity (MICs, 1.55% and 0.78% [w/v] for P. aeruginosa ATCC 27853 and E. coli ATCC 25922 respectively) than the Japanese RJ used in this study (Table 1). Therefore, further studies are needed to verify the universality of our results in M. plutonius strains belonging to different sequence types and clonal complexes and RJ originating from bee strains differing in their genetic background.…”
Section: Discussionmentioning
confidence: 63%
“…Conversely, fresh RJ purchased in Brazil and used by Nascimento et al . () appeared to exhibit stronger antimicrobial activity (MICs, 1.55% and 0.78% [w/v] for P . aeruginosa ATCC 27853 and E .…”
Section: Discussionmentioning
confidence: 99%
“…RJ is also an important functional substance that has been widely used in commercial products, dietary supplements, and cosmetics [2]. RJ has been shown to possess versatile bioactive properties such as antibacterial [3], immunomodulatory [4], antiviral [5], wound-healing [6], growth promoting [7], antioxidant [8], nephroprotective [9], and anti-inflammatory [10] activities. Fresh RJ consists of water (50–60%), lipids (3–8%), proteins (18%), carbohydrates (7–18%), and other trace elements [11].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly Algerian royal jelly was shown to have inhibitory efficacy against P. aeruginosa, and that this activity could be further enhanced by combining royal jelly with honey 106 . It is interesting to note that although the AMP royalisin is only reported to have activity against Gram positive bacteria, non-extracted samples of royal jelly have reported activity against Gram negative bacteria 107 . Similarly, Bíliková and colleagues 103 reported that royal jelly showed a strong antifungal activity against Botrytis cinerea, however extracted royalisin was only active against the fungi at concentrations of over 27 µg/ml.…”
Section: Antimicrobial Properties Of Royal Jellymentioning
confidence: 99%